How to talk to your child about drugs - Bowden-Jones, Owen (Cambridge University Press, 2025)
Broaching the topic of drugs and drug use with your child can feel particularly daunting. With the illegal drug market constantly evolving, it can be difficult to stay up to date with the latest information. How to Talk to Your Child About Drugs is an evidence-based, practical guide from a leading addiction specialist. The book offers clear and accessible guidance for parents on how to have effective conversations with their child about this difficult topic. It provides a summary of both established and newly emerging drugs, how drugs work in the brain, how they cause harm, and why some people are more vulnerable than others to problems, including signs parents should be looking out for. This is a book that all parents will need at some stage. It will help you feel better informed about drugs, more confident in talking to your child, and better equipped to tackle any problems.